Internal nasal morphology of the Eocene primate Rooneyia viejaensis and extant Euarchonta: Using μCT scan data to understand and infer patterns of nasal fossa evolution in primates. Issue 132 (July 2019) - Lundeen, Ingrid K.; Kirk, E. Christopher
Abstract: Primates have historically been viewed as having a diminished sense of smell compared to other mammals. In haplorhines, olfactory reduction has been inferred partly based on the complexity of the bony turbinals within the nasal cavity. Some turbinals are covered in olfactory epithelium, which contains olfactory receptor neurons that detect odorants. Accordingly, turbinal number and complexity has been used as a rough anatomical proxy for the relative importance of olfactory cues for an animal's behavioral ecology. Unfortunately, turbinals are delicate and rarely preserved in fossil specimens, limiting opportunities to make direct observations of the olfactory periphery in extinct primates. Here we describe the turbinal morphology of Rooneyia viejaensis, a late middle Eocene primate of uncertain phylogenetic affinities from the Tornillo Basin of West Texas. This species is currently the oldest fossil primate for which turbinals are preserved with minimal damage or distortion. Microcomputed tomography (μCT) reveals that Rooneyia possessed 1 nasoturbinal, 4 bullar ethmoturbinals, 1 frontoturbinal, 1 interturbinal, and an olfactory recess. This pattern is broadly similar to the condition seen in some extant strepsirrhine primates but differs substantially from the condition seen in extant haplorhines. Crown haplorhines possess only two ethmoturbinals and lack frontoturbinals, interturbinals, and an olfactory recess. Additionally, crown anthropoids have ethmoturbinals that are non-bullar. These observations reinforce the conclusion that Rooneyia is not a stem tarsiiform or stem anthropoid. However, estimated olfactory turbinal surface area in Rooneyia is greater than that of similar-sized haplorhines but smaller than that of similar-sized lemuriforms and lorisiforms. This finding suggests that although Rooneyia was broadly plesiomorphic in retaining a large complement of olfactory turbinals as in living strepsirrhines, Rooneyia may have evolved somewhat diminished olfactory abilities as in living haplorhines.